Defining the pubic symphysis angle with respect to the coronal plane — Clinical and biomechanical considerations. Issue 7 (July 2017) - Link, B.-C.; Ha, N.B.; Solomon, L.B.; Rickman, M.
Abstract: Background: Fixation strength of constructs placed across the pubic symphysis after injury is dependent on screw length, maximisation of which requires knowledge of the bony anatomy. The aim of this study was to describe the ideal angle of drilling to achieve maximal safe screw placement within the pubic body. Furthermore, the influences of age and gender on the skeletal topography were investigated. Methods: Three hundred CT scans of patients without pelvic injury were analysed to record the angle of the pubic body (APB) with respect to the coronal plane, and the depth of the pubic body (DPB) in the sagittal plane. Results: Mean APB and DPB were 54.69° and 55.35 mm, respectively. Females had a significantly higher mean APB than males (57.29° vs. 52.41°; p < 0.001), whereas males had a significant larger mean DPB (59.13 mm vs. 51.03 mm; p < 0.001). Age had no effect on the mean APB. Mean width of the pubic body at the base was 9.38 mm. Conclusion: The anatomy of this region is reliable in terms of angles and sizes; a drill angle of 55° with respect to the operating table will allow maximal screw length, which should be in the region of 55 mm. The mean width of the pubic body should allow for placement of a 3.5 or 4.5 mm diameter screw.